Power Loss Modes of Building-Integrated Photovoltaic Modules: An Analytical Approach Using Outdoor I - V Curves - Gök, Abdülkerim; Ozkalay, Ebrar; Friesen, Gabi; Frontini, Francesco (IEEE-Inst Electrical Electronics Engineers Inc, 2021)
Using outdoor time-series I-V curves, the analytic I-sc-V-oc method was applied to glass/backsheet and glass/glass crystalline silicon module constructions with ventilated and insulated mounting configurations in order to explore contributing factors to degradation in the power performance. The rates of power loss modes; namely uniform current, recombination, series resistance, and current mismatch, were assessed for each module and configuration. The effect of thermal insulation was evident in the glass/backsheet module with an ethylene-vinyl acetate type encapsulant: the observed loss in the performance was chiefly originated from the resistive loss. The cell and metallization defects induced by thermo-mechanical stresses were believed to be main reasons. However, the double glass module with a polyvinyl-butyral type encapsulant was more resistant to thermal effects: a large increase in the uniform current, compensated by the resistive loss, was the main driver for the observed gain in the performance. For all modules and configurations, the calculated power loss mode rates were compared with the reported performance loss rates and they were found to be in close agreement. This analytic technique was found to be a powerful method in order to determine and quantify the individual contributions from specific power loss modes to overall module performance.
Keywords: Analytic I-sc-V-oc method; building-integrated photovoltaics (BIPV); outdoor I - V curves; power loss modes; thermal insulation; year-over-year (YoY) regression